Concurrent anomaly of right renal and testicular vein - Jeyaseelan, Nadankutty; Sundarapandian, S. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
Concurrent venous anomalies were observed during routine dissection of the posterior abdominal wall in a 55 year old male cadaver. The right renal vein was double;0ne upper right renal vein (URRV) and one lower right renal vein (LRRV). Concurrently, the right testicular vein (RTV) drained into the LRRV. These anomalies if unidentified can lead to morbidity during surgical exploration. The knowledge of these anatomic variations in the retroperitoneal region is of importance to both surgeons and invasive radiologists.